Effect of pathologist's dedication on lymph node detection rate and postoperative survival in colorectal cancer. (14th May 2018) - Unger, L. W.; Muckenhuber, M.; Riss, S.; Argeny, S.; Stift, J.; Mesteri, I.; Stift, A.
Abstract: Aim: As adjuvant chemotherapy in colorectal cancer relies on the identification of lymph node metastases, the pathologist's dedication may have a considerable influence on postoperative survival. Method: The aim of this retrospective study was to assess the impact of the pathologist's dedication on lymph node detection rate and postoperative survival in patients operated on by a single experienced colorectal surgeon within a 5‐year period. We assessed 229 patients undergoing total mesorectal excision or complete mesocolic excision by the senior author between 1 January 2009 and 31 December 2013. Pathologists were grouped as 'general pathologist' or 'dedicated pathologist' depending on their dedication/specialization. Results: Dedicated pathologists found statistically significantly more lymph nodes in colorectal specimens than general pathologists [23 (interquartile range 24) vs 14 (interquartile range 11), respectively; P < 0.001]. The detection rate of ≥ 12 lymph nodes per specimen was significantly higher in the dedicated pathologist group [65/74 (87.8%) vs 105/155 (67.7%); P = 0.016]. However, postoperative survival did not differ in the respective subgroups. In the multivariable analysis by Cox proportional hazard model, International Union against Cancer Stage IV was the only factor associated with decreased disease‐specific survival (hazard ratio 28.257; 95% CI 3.850–207.386; P = 0.001). Conclusion: In our centre, the pathologist's dedication has an impact on lymph node detection rate but does not influence postoperative disease‐specific survival.